2021
DOI: 10.1021/acs.cgd.1c00884
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Blue Emissive Neutral Cu(I) Complexes: Structural Analysis, Thermochromic Luminescent Properties, and Terahertz Spectrum Research

Abstract: Herein, we report six neutral Cu(I) halide complexes based on [CuX(BIM)(P^P)] (P^P, diphosphine ligands; BIM, 1-butylimmidazole) with intense blue emission. When diphosphine ligands (POP, bis(2-(diphenylphosphino)phenyl)ether; Xantphos (4,5-bis(diphenylphosphino)-9,9-dimethylxanthene)), BIM and CuX (X = I, Br, Cl) were mixed in solution, pure and high yield products were obtained. Single crystal X-ray diffraction showed that each complex was of copper-centered tetrahedral structure. Different weak interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The single band blue emission can be assigned to the mixture of high-lying metal-to-ligand charge transfer (MLCT) and halogen-to-ligand charge transfer (XLCT) excited states. 57–62…”
Section: Resultsmentioning
confidence: 99%
“…The single band blue emission can be assigned to the mixture of high-lying metal-to-ligand charge transfer (MLCT) and halogen-to-ligand charge transfer (XLCT) excited states. 57–62…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorus ligand used in this study is the same as that in previous work, namely POP. 38 However, the nitrogen ligands differ, resulting in significant differences in the luminescent properties. Based on theoretical investigations, we found that the LUMO of the complexes are primarily composed of the nitrogen ligands, while the HOMO-6 and HOMO-3 are composed of the metal, halogen atoms, and phosphorus ligands.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Following our previous work, we retained the rigid ligand POP that contributes to luminescence, to ensure that the complexes in this work also have a high quantum yield similar to that of the previous work. 38 The nitrogen ligand has been replaced with bipy, the elevation of the LUMO energy has resulted in a decrease in the HOMO-6–LUMO (for 1 and 2 ) and HOMO-3–LUMO (for 3 ) energy gaps, resulting in a redshift in the emission position of the complexes from blue to yellow light emission. Furthermore, we investigated the influence of weak interactions for the complexes on the luminescent properties.…”
mentioning
confidence: 99%